The future of factional politics in China under Xi Jinping - Lee, Jonghyuk (2023)
The recent leadership reshuffle in the Communist Party of China reflects a significant departure from the longstanding tradition of balancing factional politics and working collectively on an overarching goal to buttress control across the party’s membership and bureaucratic structure on the ground. With Xi Jinping’s approach, officials compete with each other in a bid to gain favour. Unfortunately, this could come at the cost of stifling local initiatives, which have historically played a significant role in China’s progress.